Safety and efficacy of current alternatives in the topical treatment of cutaneous leishmaniasis: a systematic review. Issue 8 (3rd April 2017) - WOLF NASSIF, PRISCILA; DE MELLO, TATIANE FRANÇA PERLES; NAVASCONI, TAÍSA ROCHA; MOTA, CAMILA ALVES; DEMARCHI, IZABEL GALHARDO; ARISTIDES, SANDRA MARA ALESSI; LONARDONI, MARIA VALDRINEZ CAMPANA; TEIXEIRA, JORGE JUAREZ VIEIRA; SILVEIRA, THAÍS GOMES VERZIGNASSI
SUMMARY: Studies of topical treatments for leishmaniasis were systematically reviewed, to evaluate the therapeutic efficacy, safety and any adverse effects of these treatments. The papers identified in the databases PubMed and Web of Knowledge involved eight studies with a total of 1744 patients. The majority of trials was from Iran (4/8), covered a period of 8 years (2003–2011), and included patients 4–85 years of age. The most frequent Leishmania species in the studies were L. tropica (4/8) and L. major (2/8). The treatments administered were thermotherapy, paromomycin and combinations, CO2 laser, 5-aminolevulinic acid hydrochloride (10%) plus visible red light (633 nm) and cryotherapy. Six articles reported cure rates over 80·0%. Six studies reported on failure rates, three of them reporting rates lower than 10%. Four studies did not report relapses or recurrences, while the other studies reported low rates (1·8–6·3%). The most common adverse effects of the topical treatments were redness/erythema, pain, pruritus burning, oedema, vesicles and hyper- or hypopigmentation. The results provide strong evidence that the treatments topical evaluated showed high cure rates, safety and effectiveness, with low side-effects, relapse and recurrence rates, except for cryotherapy, which showed a moderate cure rate.